Characterisation of pulmonary arterial hypertension patients with cardiovascular comorbidities treated with selexipag: real-world evidence from the EXPOSURE study. (3rd October 2022) - Soderberg, S; Gaine, S; Muller, A; Klement, R; Lange, T; Escribano, P
Abstract: Background: A recent post-hoc analysis of the GRIPHON randomised controlled trial [1] showed that selexipag reduces the risk of a morbidity/mortality event versus placebo in pulmonary arterial hypertension (PAH) patients, irrespective of comorbidity burden. Real-world evidence is needed on the management of PAH patients with cardiovascular comorbidities receiving selexipag. Purpose: To describe characteristics, treatment patterns and outcomes of PAH patients with cardiovascular comorbidities receiving selexipag in the real world. Methods: EXPOSURE is an ongoing, multicentre, prospective, observational study of PAH patients initiating a PAH-specific therapy in Europe and Canada. Patients initiating selexipag were grouped by number of cardiovascular comorbidities present prior to or at therapy initiation: BMI ≥30 kg/m 2, systemic hypertension, diabetes mellitus, and coronary artery disease. Results: As of November 2020, 382 selexipag-treated patients had follow-up and comorbidity data available: 44% (n=169) had 0, 30% (n=114) had 1, 18% (n=70) had 2, and 8% (n=29) had ≥3 comorbidities. At selexipag initiation, patients with comorbidities were older, more likely to have idiopathic/heritable PAH and had worse functional capacity (lower median 6-minute walk distance, higher proportion in WHO functional class III/IV) vs those without comorbidities (Table 1). Overall, haemodynamic parameters were similar across groups (Table 1). Patients with a higher comorbidity burden were more likely to be at high-risk of 1-year mortality (COMPERA method) vs those with a lower comorbidity burden (Table 1). Patients predominantly initiated selexipag as part of triple combination therapy (mainly in addition to an endothelin receptor antagonist and phosphodiesterase type 5 inhibitor), regardless of comorbidity burden (76–79% across groups). The duration of exposure and the median selexipag maintenance dose were similar across groups (Table 2). The proportion of patients hospitalised and the proportion who discontinued selexipag during the exposure period are shown in Table 2. 5% (n=8) of patients in the 0 comorbidities group, 12% (n=14) in the 1 comorbidity group, 0% in the 2 comorbidities group, and 10% (n=3) in the ≥3 comorbidities group died during the exposure period. Conclusions: These real-world data from Europe and Canada suggest that more than 50% of patients who initiated selexipag had ≥1 cardiovascular comorbidity. Patients with comorbidities had more severe functional impairment vs those without. Overall haemodynamic profiles reflected Group 1 Pulmonary Hypertension and were similar across groups. Selexipag was initiated predominantly as part of triple combination therapy in all groups and most patients remained on selexipag, regardless of comorbidity burden. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Actelion Pharmaceuticals Ltd, a Janssen Pharmaceutical Company of Johnson & Johnson